2017
DOI: 10.1016/j.mambio.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Weak premating isolation between two parapatric brocket deer species

Abstract: Brocket deer Mazama nemorivaga and M. gouazoubira occur at the Amazon basin and southern areas, respectively, in parapatric distribution ranges. Both species can interbreed in captivity, although hybrids have serious fertility problems. Therefore, we expect natural selection to favour behavioural barriers against interspecific mating. We carried out no-choice tests with individuals of both species in captivity, along with white-tailed deer (Odocoileous virginianus) as outgroup. Behaviours were video recorded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Since the pre-zygotic reproductive barrier between MNE and MGO is fragile [ 63 ], the post-zygotic barrier for sterility of the hybrid seems to keep these two species isolated and evolving independently. Even with wide geographical contact between the Amazon (MNE habitat) and the Cerrado (MGO habitat) for more than 2000 km.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the pre-zygotic reproductive barrier between MNE and MGO is fragile [ 63 ], the post-zygotic barrier for sterility of the hybrid seems to keep these two species isolated and evolving independently. Even with wide geographical contact between the Amazon (MNE habitat) and the Cerrado (MGO habitat) for more than 2000 km.…”
Section: Discussionmentioning
confidence: 99%
“…We report the first production of hybrids between MGO and MNE, which were viable until maturity, but presumably infertile. There are no reports of hybrids in the wild, although a weak pre-mating isolation barrier between species has been observed in captivity [ 63 ]. Regarding MAM, reports of captive crossbreeding between cytotypes already exist [ 25 , 75 ], which are explained by the verified lack of a clear pre-mating barrier [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The craniometric study of Rossi (2000), that included an extensive sampling of brocket deer species failed to distinguish two different species of red brockets deer (M. americana and M. bororo) but discriminated by canonical analysis the two gray brockets (M. gouazoubira and M nemorivaga). As a part of an integrative project, Carranza et al (2017) found evidence revealing weak premating behaviour isolation between M. gouazoubira and M nemorivaga, being more common at intraspecific interactions and suggesting discrimination between species.…”
Section: Comparative Craniometrical Studymentioning
confidence: 97%
“…In a recent study with brocket deer of the grey clade, interspecific matings between M. gouazoubira and M. nemorivaga occurred in almost 36% of trials (Carranza et al, 2017). These species are morphologically convergent and also show several copulations within the same ovulation, so chances for post-mating sexual selection appear also high (Carranza et al, 2017). Postmating-prezygotic mechanisms have been shown to effectively reduce gene flow and thus act to maintain species boundaries if fertilization success in conspecific matings is relatively greater than that in heterospecific ones (Howard et al, 1998(Howard et al, , 2009.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent study with brocket deer of the grey clade, interspecific matings between M. gouazoubira and M. nemorivaga occurred in almost 36% of trials (Carranza et al, 2017). These species are morphologically convergent and also show several copulations within the same ovulation, so chances for post-mating sexual selection appear also high (Carranza et al, 2017).…”
Section: Discussionmentioning
confidence: 99%